2016
DOI: 10.1097/md.0000000000003804
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the different pH-metry scores in gastroesophageal reflux disease in children

Abstract: The 24-hour esophageal pH-metry is the most widely used method to diagnose the gastroesophageal reflux disease (GERD). The study compares the different scores obtained during the 24-hour esophageal pH-metry. A retrospective study over 5 years including 234 children (1 month and 18 years old) admitted in a pediatric gastroenterology regional center in Northeast Romania, with suspicion of GERD. They underwent 24- hour esophageal pH-metry, and the scores obtained (Boix-Ochoa, DeMeester, Johnson-DeMeester) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…The aspects concerning the potential adverse events, quality of life and vulnerabilities, must be carefully approached. The risk and resilience factors must be known and evaluated and the the therapeutic approach must be ethical with the lowest number of adverse events encountered [42][43][44][45][46]. We must be careful and also prevent the emergence of metabolic abnormalities [47][48][49][50][51][52][53][54].…”
Section: Results Of the Metabolic Abnormalities Investigationsmentioning
confidence: 99%
“…The aspects concerning the potential adverse events, quality of life and vulnerabilities, must be carefully approached. The risk and resilience factors must be known and evaluated and the the therapeutic approach must be ethical with the lowest number of adverse events encountered [42][43][44][45][46]. We must be careful and also prevent the emergence of metabolic abnormalities [47][48][49][50][51][52][53][54].…”
Section: Results Of the Metabolic Abnormalities Investigationsmentioning
confidence: 99%
“…Considering cancer as a dynamic process, in which the tumor cells profile is dysregulated, early detection and cure is not always possible; in recent years has been widely discussed the proper approach of cancer therapy. It is a general tendency to try to control the disease, relieving the symptoms and prolonging patients life [13,14]. On the other hand, one might expect that deciphering all the mechanisms involved in pathophysiological conditions would lead to a better way of assuming a new attitude towards cancer therapy, determining cancer outcome [15,16].…”
mentioning
confidence: 99%
“…Lupu et al have demonstrated that high sensitivity and specificity of all three scores, as well as very high correlation between DeMeester and Boix-Ochoa score (r = 0.978, p<0.01, 95% CI), suggesting that they may equally be used in pH studies (23). Johnson-DeMeester score showed a greater risk of false-negative results (23).…”
Section: Combined Ph-mii Monitoring: Advantages and Disadvantagesmentioning
confidence: 99%